Analgosedation in cardiology. DGK and DGAI consensus paper 2024 Analgosedierung in der Kardiologie Konsensuspapier der DGK und DGAI 2024 - Tilz, R. R.; Busch, S.; Chun, K. R.J.; Frerker, C.; Gaede, Luise; Steven, D.; Tiefenbacher, C.; Eckardt, L.; Sander, M.; Zwißler, B.; Wappler, F.; von Dossow, V.; et al. (Anästhesiologie & Intensivmedizin, 2024)
Interventions in electrophysiology and interventional cardiology are increasingly common. Many of these interventions are performed under sedation. This is necessary to ensure the patient’s comfort and safety to facilitate transesophageal echocardiography, pain control, or long procedure duration, e.g., with stable mapping conditions. This consensus document by the German Cardiac Society (DGK) together with the German Association of Anesthesia and Intensive Care (DGAI) describes – based on current evidence – the structured pathways for sedation in cardiovascular medicine. The major goal is patient safety for patients undergoing electrophysiology and endovascular cardiovascular procedures. This consensus document is also aligned to the published German S3 guideline for sedation in gastroenterology.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Atrial fibrillation; Catheter ablation; Defibrillators; implantable; Mitraclip; Pacemaker; artificial

Analgosedierung in der Kardiologie - Konsensuspapier der DGK und DGAI 2024 - Tilz, Roland R.; Busch, Sonia; Chun, K. R.J.; Frerker, Christian; Gaede, Luise; Steven, Daniel; Tiefenbacher, Christiane; Eckardt, Lars; Sander, Michael; Zwißler, Bernhard; Wappler, Frank; von Dossow, Vera; et al. (Die Kardiologie, 2024)
Interventions in electrophysiology and interventional cardiology are increasingly common. Many of these interventions are performed under sedation. This is necessary to ensure the patient’s comfort and safety to facilitate transesophageal echocardiography, pain control, or long procedure duration, e.g., with stable mapping conditions. This consensus document by the German Cardiac Society (DGK) together with the German Association of Anesthesia and Intensive Care (DGAI) describes—based on current evidence—the structured pathways for sedation in cardiovascular medicine. The major goal is patient safety for patients undergoing electrophysiology and endovascular cardiovascular procedures. This consensus document is also aligned to the published German S3 guideline for sedation in gastroenterology.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Atrial fibrillation; Catheter ablation; Defibrillators; implantable; Mitraclip; Pacemaker; artificial

Answer to the letter of Dr. Bestehorn - Gaede, Luise; Möllmann, Helge (Clinical Research in Cardiology, 2022)
CRIS-Team Scopus Importer:2022-12-02

Bifurcation lesions: Are new strategies and devices needed? Bifurkationsläsionen: Braucht es neue Strategien und Devices? - Gaede, Luise (Herz, 2022)
Interventional treatment of bifurcation lesions, especially true complex bifurcation lesions, continue to be a challenge for interventional cardiologists. A primary one stent strategy is always preferred for simple bifurcation lesions, whereas studies in recent years have shown that a two stent strategy may be advantageous for true bifurcations, i.e. those involving at least the distal main branch as well as the side branch. This seems to be even more pronounced when the lesion presents as complex, i.e., the side branch shows high-grade stenosis over longer stretches and the complete lesion fulfils certain criteria, e.g., severe calcification and a bifurcation angle < 45° or > 70°. According to the latest randomized trials and meta-analyses, the double kissing (DK) crush and double kissing mini-crush (DKMC) techniques in particular seem to be advantageous for these lesions; however, in recent years the established techniques have been continuously refined and further developed. The DK culotte technique and the nano-crush technique deserve special attention. Both techniques seem to further improve and simplify the existing underlying strategies; however, further studies to prove the superiority of these techniques over the established ones are still pending. Overall, the implementation of the available randomized study results, the further development of the techniques and also of the materials can continuously improve the outcome of the patients after interventional treatment of bifurcation lesions. This is also confirmed by the latest registry data, which for the first time could show equal event rates in patients after treatment of complex lesions compared to simple lesions in the clinical practice.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Coronary vessels; Culotte technique; DK crush technique; Stent strategies; Stent techniques

Comparison of adenosine-independent pressure indices to fractional flow reserve in stent-jailed bifurcation side branches - Altstidl, Johannes Michael; Achenbach, Stephan; Marwan, Mohamed; Tröbs, Monique; Schacher, Nora; Ferstl, Paul; Gerlach, Andreas; Schlundt, Christian; Gaede, Luise (Catheterization and Cardiovascular Interventions, 2022)
Objectives and Background: This study aims to evaluate whether the high correlation and classification agreement of the instantaneous wave-free ratio (iFR) and the resting distal coronary to aortic pressure ratio (Pd/Pa) with the fractional flow reserve (FFR) can be confirmed in stent-jailed side branches (J-SB). Methods: Consecutive patients (n = 49) undergoing provisional stenting were prospectively enrolled and a physiological assessment of the J-SB (n = 51) was performed. FFR, iFR, and Pd/Pa were measured and the hemodynamic relevance was determined using cutoff values of ≤0.80, ≤0.89, and ≤0.92, respectively. Results: Both iFR (r = 0.75) and Pd/Pa (r = 0.77) correlated closely with FFR. Classification agreement with FFR was 78% for iFR (81% sensitivity, 77% specificity) and 75% for Pd/Pa (63% sensitivity and 80% specificity). However, angiographic diameter stenosis and pressure indices correlated poorly. For a threshold of ≥70% stenosis, agreement concerning hemodynamic relevance was found in 59% for FFR, 69% for iFR, and 61% for Pd/Pa. Conclusion: As reported for other lesion types, FFR and the adenosine-independent pressure indices iFR and Pd/Pa show close correlation and a high classification agreement of approximately 75%–80% in J-SB. Therefore, iFR can be regarded as a recommendable alternative to FFR for the guidance of provisional stenting in bifurcation lesions.
CRIS-Team Scopus Importer:2022-07-01
Keywords: catheterization diagnostic; coronary artery disease; fractional flow reserve

Comparison of Coronary Intravascular Lithotripsy and Rotational Atherectomy in the Modification of Severely Calcified Stenoses - Blachutzik, Florian; Meier, Sophie; Weissner, Melissa; Schlattner, Sophia; Gori, Tommaso; Ullrich-Daub, Helen; Gaede, Luise; Achenbach, Stephan; Möllmann, Helge; Chitic, Bogdan; Aksoy, Adem; Nickenig, Georg; et al. (American Journal of Cardiology, 2023)
Debulking techniques are often necessary for successful lesion preparation in percutaneous coronary intervention. The aim of this study was to compare plaque modification of severely calcified lesions by coronary intravascular lithotripsy (IVL) with that of rotational atherectomy (RA) using optical coherence tomography (OCT). ROTA.shock was a 1:1 randomized, prospective, double-arm, multicenter noninferiority trial designed to compare final minimal stent area after IVL with RA for lesion preparation in percutaneous coronary interventional treatment of severely calcified lesions. On the basis of OCT acquired before and immediately after IVL or RA in 21 of the 70 patients included, we performed a detailed analysis of the modification of the calcified plaque. After RA and IVL, calcified plaque fractures were present in 14 of the patients (67%), with a significantly greater number of fractures after IVL (3.23 ± 0.49) than after RA (1.67 ± 0.52; p < 0.001). Plaque fractures after IVL were longer than after RA (IVL: 1.67 ± 0.43 mm vs RA: 0.57 ± 0.55 mm; p = 0.01), resulting in a greater total volume of the fractures (IVL: 1.47 ± 0.40 mm3 vs RA: 0.48 ± 0.27 mm3; p = 0.003). Use of RA was associated with a greater acute lumen gain than was use of IVL (RA: 0.46 ± 0.16 mm2 vs IVL: 0.17 ± 0.14 mm2; p = 0.03). In conclusion, we were able to show differences in plaque modification of calcified coronary lesions by OCT: although RA leads to a greater acute lumen gain, IVL induces more and longer fractures of the calcified plaque.
CRIS-Team Scopus Importer:2023-04-07

Comparison of interventional treatment options for coronary calcified nodules: A sub-analysis of the ROTA.shock trial - Blachutzik, Florian; Meier, Sophie; Blachutzik, Melissa; Schlattner, Sophia; Gori, Tommaso; Ullrich-Daub, Helen; Gaede, Luise; Achenbach, Stephan; Möllmann, Helge; Chitic, Bogdan; Aksoy, Adem; Nickenig, Georg; et al. (Cardiovascular Revascularization Medicine, 2024)
Background: The optimal treatment for coronary calcified nodules (CNs) is still unclear. The aim of this study was to compare the modification of these lesions by coronary intravascular lithotripsy (IVL) and rotational atherectomy (RA) using optical coherence tomography (OCT). Methods: ROTA.shock was a 1:1 randomized, prospective, double-arm multi-center non-inferiority trial that compared the use of IVL and RA with percutaneous coronary intervention (PCI) in severely calcified lesions. In 19 of the patients out of this study CNs were detected by OCT in the target lesion and were treated by either IVL or RA. Results: The mean angle of CNs was significantly larger in final OCT scans than before RA (92 ± 17° vs. 68 ± 7°; p = 0.01) and IVL (89 ± 18° vs. 60 ± 10°; p = 0.03). The CNs were thinner upon final scans than in initial native scans (RA: 17.8 ± 7.8 mm vs. 38.6 ± 13.1 mm; p = 0.02; IVL: 16.5 ± 9.0 mm vs. 37.2 ± 14.3 mm; p = 0.02). Nodule volume did not differ significantly between native and final OCT scans (RA: 0.66 ± 0.12 mm3 vs. 0.61 ± 0.33 mm3; p = 0.68; IVL: 0.64 ± 0.19 mm3 vs. 0.68 ± 0.22 mm3; p = 0.74). Final stent eccentricity was high with 0.62 ± 0.10 after RA and 0.61 ± 0.09 after IVL. Conclusion: RA or IVL are unable to reduce the volume of the calcified plaque. CN modulation seems to be mainly induced by the stent implantation and not by RA or IVL.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Calcified nodules; Intravascular imaging; Intravascular lithotripsy; Percutaneous coronary intervention; Rotational atherectomy

Coronary intravascular lithotripsy and rotational atherectomy for severely calcified stenosis: Results from the ROTA.shock trial - Blachutzik, F.; Meier, S.; Weissner, M.; Schlattner, S.; Gori, T.; Ullrich, H.; Gaede, Luise; Achenbach, Stephan; Möllmann, H.; Chitic, B.; Aksoy, A.; Nickenig, G.; et al. (Catheterization and Cardiovascular Interventions, 2023)
Background: Severely calcified coronary lesions present a particular challenge for percutaneous coronary intervention. Aims: The aim of this randomized study was to determine whether coronary intravascular lithotripsy (IVL) is non-inferior to rotational atherectomy (RA) regarding minimal stent area (MSA). Methods: The randomized, prospective non-inferiority ROTA.shock trial enrolled 70 patients between July 2019 and November 2021. Patients were randomly (1:1) assigned to undergo either IVL or RA before percutaneous coronary intervention of severely calcified coronary lesions. Optical coherence tomography was performed at the end of the procedure for primary endpoint analysis. Results: The primary endpoint MSA was lower but non-inferior after IVL (mean: 6.10 mm2, 95% confidence interval [95% CI]: 5.32–6.87 mm2) versus RA (6.60 mm2, 95% CI: 5.66–7.54 mm2; difference in MSA: −0.50 mm2, 95% CI: −1.52–0.52 mm2; non-inferiority margin: −1.60 mm2). Stent expansion was similar (RA: 0.83 ± 0.10 vs. IVL: 0.82 ± 0.11; p = 0.79). There were no significant differences regarding contrast media consumption (RA: 183.1 ± 68.8 vs. IVL: 163.3 ± 55.0 mL; p = 0.47), radiation dose (RA: 7269 ± 11288 vs. IVL: 5010 ± 4140 cGy cm2; p = 0.68), and procedure time (RA: 79.5 ± 34.5 vs. IVL: 66.0 ± 19.4 min; p = 0.18). Conclusion: IVL is non-inferior regarding MSA and results in a similar stent expansion in a random comparison with RA. Procedure time, contrast volume, and dose-area product do not differ significantly.
CRIS-Team Scopus Importer:2023-09-15
Keywords: calcified stenosis; drug-eluting stent; optical coherence tomography; rotational atherectomy

Crystalline sirolimus-coated balloon (cSCB) angioplasty in an all-comers, patient population with stable and unstable coronary artery disease including chronic total occlusions: rationale, methodology and design of the SCORE trial - Otto, Sylvia; Diaz, Victor Alfonso Jimenez; Weilenmann, Daniel; Cuculi, Florim; Nuruddin, Amin Ariff; Leibundgut, Gregor; Alfonso, Fernando; Wan Ahmad, Wan Azman; Pyxaras, Stylianos; Rittger, Harald; Steen, Philip; Gaede, Luise; et al. (Bmc Cardiovascular Disorders, 2023)
BackgroundA decade ago, the iopromide-paclitaxel coated balloon (iPCB) was added to the cardiologist's toolbox to initially treat in-stent restenosis followed by the treatment of de novo coronary lesions. In the meantime, DES technologies have been substantially improved to address in-stent restenosis and thrombosis, and shortened anti-platelet therapy. Recently, sirolimus-coated balloon catheters (SCB) have emerged to provide an alternative drug to combat restenosis.MethodsThe objective of this study is to determine the safety and efficacy of a novel crystalline sirolimus-coated balloon (cSCB) technology in an unselective, international, large-scale patient population. Percutaneous coronary interventions of native stenosis, in-stent stenosis, and chronic total occlusions with the SCB in patients with stable coronary artery disease or acute coronary syndrome were included. The primary outcome variable is the target lesion failure (TLF) rate at 12 months, defined as the composite rate of target vessel myocardial infarction (TV-MI), cardiac death or ischemia-driven target lesion revascularization (TLR). The secondary outcome variables include TLF at 24 months, ischemia driven TLR at 12 and 24 months and all-cause death, cardiac death at 12 and 24 months.DiscussionSince there is a wealth of patient-based all-comers data for iPCB available for this study, a propensity-score matched analysis is planned to compare cSCB and iPCB for the treatment of de novo and different types of ISR. In addition, pre-specified analyses in challenging lesion subsets such as chronic total occlusions will provide evidence whether the two balloon coating technologies differ in their clinical benefit for the patient.
CRIS-Team WoS Importer:2023-04-21

Double kissing - crush technique to treat coronary bifurcation lesions: analysis of success rate, procedural times and device usage - Schacher, Nora; Ferstl, Paul; Weidinger, Franz; Achenbach, Stephan; Tröbs, Monique; Marwan, Mohamed; Gaede, Luise (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Glossary of process times and key indicators in the cardiac catheterization laboratory: CCL glossary Glossar zu Prozesszeiten und Kennzahlen im Herzkatheterlabor: HKL-Glossar - Dörr, Oliver; Schuster, Martin; Gaede, Luise; Ghanem, Alexander; Schmitz, Thomas; Hamm, Christian (Die Kardiologie, 2023)
The demographic change and innovative advances in interventional cardiology lead to changes in the quality of the medical care for patients with cardiovascular diseases. A successful management of cardiac catheterization laboratories can result in an efficiency-oriented organization of medical service processes as well as a robust reporting system, whereby healthcare and economic goals do not have to be in conflict. By establishing and standardizing process steps, process indicators can be derived to help improve the quality of care for patients with cardiovascular diseases.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Health economy; Hospital management; Process steps; Quality of care; Service processes

Impact of COVID-19 lockdown on the procedural and intra-hospital outcome of STEMI patients - Gaede, Luise; Rittger, H.; Gerrens, H.; Achajew, A.; Schacher, Nora; Ferstl, Paul; Tröbs, Monique; Arnold, Martin; Marwan, Mohamed; Achenbach, Stephan (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Influence of sex on results and consequences of coronary fractional flow reserve in clinical practice: results of a prospective large-scale multicenter registry - Tröbs, Monique; Marwan, Mohamed; Gaede, Luise; Moellmann, H.; Giesler, T.; Rittger, H.; Rudolph, T.; Pauschinger, M.; Moshage, W.; Brueck, M.; Achenbach, Susanne (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

In-hospital Outcomes of Rotational Atherectomy in ST-Elevation Myocardial Infarction: Results From the Multicentre ROTA-STEMI Network - Hemetsberger, Rayyan; Mankerious, Nader; Muntané-Carol, Guillem; Temporal, Justin; Sulimov, Dmitriy; Gaede, Luise; Woitek, Felix; Grau, Edgar Fadeuilhe; Scalamogna, Maria; Olschewski, Maximilian; Mitsis, Andreas; Ruzsa, Zoltán; et al. (Canadian Journal of Cardiology, 2024)
Background: Although the use of rotational atherectomy (RA) is off-label in the setting of ST-elevation myocardial infarction (STEMI), it can be the only option in severely calcified culprit lesions to achieve procedural success. We sought to investigate the safety and feasibility of RA during primary percutaneous coronary intervention (PPCI). Methods: This was a retrospective observational study of patients who underwent RA during PPCI from 12 European centres. The main outcomes were procedural success (defined as successful stent implantation with final thrombolysis in myocardial infarction [TIMI] flow 3 and residual stenosis < 30%) and in-hospital mortality. A comparison of patients presenting with and without shock was performed. Results: In 104 patients with RA during STEMI, the mean age was 72.8 ± 9.1 years, and 35% presented with cardiogenic shock. Bailout RA was performed in 76.9% of cases. Mean burr size was 1.42 ± 0.21 mm. Procedural success was achieved in 86.5% of cases, with no difference between shocked and nonshocked patients (94.4% vs 82.4%; P = 0.13). In-hospital stent thrombosis occurred in 0.96%, perforation in 1.9% and burr entrapment in 2.9% of cases. In spite of equally high procedural success, in-hospital mortality was higher in shocked (50%) compared with nonshocked patients (1.5%; P < 0.0001). Conclusions: Patients presenting with STEMI requiring RA, represent a high-risk population, frequently presenting with cardiogenic shock. In this analysis of selected patients, RA was performed as a bailout strategy in the majority, and, as such, RA seems to be feasible with a high procedural success rate. In the absence of cardiogenic shock, RA-facilitated PCI seems to be associated with low in-hospital mortality.
CRIS-Team Scopus Importer:2024-05-03

Manual der Arbeitsgruppe Interventionelle Kardiologie (AGIK) der Deutschen Gesellschaft für Kardiologie – Herz- und Kreislaufforschung e. V. (DGK), Teil 1: „Durchführung der diagnostischen Herzkatheteruntersuchung“ - Nef, Holger M.; Achenbach, Stephan; Birkemeyer, Ralf; Bufe, Alexander; Doerr, Oliver; Elsaesser, Albrecht; Gaede, Luise; Gori, Tommaso; Hoffmeister, Hans M.; Hofmann, Felix J.; Katus, Hugo A.; Liebetrau, Christoph; et al. (Der Kardiologe, 2021)
This manual on diagnostic cardiac catheterization (part 1) is a recommendation for application by interventional cardiologists, which reflects the latest evidence in interventional cardiology. Each chapter was designed to focus on the everyday practicability and to provide decision support in the daily clinical routine of the catheter laboratory. Despite the practical advice by many experts, this manual cannot replace the medical evaluation of each individual patient and thus an adaptation of the diagnostics or treatment is necessary.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Acute coronary syndrome; Cardiovascular disease; Catheter laboratory; Coronary angiography; PCI

Manual der Arbeitsgruppe Interventionelle Kardiologie (AGIK) der Deutschen Gesellschaft für Kardiologie – Herz- und Kreislaufforschung e.V. (DGK) - Teil 2: „Durchführung der perkutanen Koronarintervention“ - Nef, Holger M.; Achenbach, Stephan; Birkemeyer, Ralf; Bufe, Alexander; Doerr, Oliver; Elsaesser, Albrecht; Gaede, Luise; Gori, Tommaso; Hoffmeister, Hans M.; Hofmann, Felix J.; Katus, Hugo A.; Liebetrau, Christoph; et al. (Der Kardiologe, 2021)
This manual addressing the interventional treatment (part 2) is a recommendation for interventional cardiologists. It displays the latest evidence in interventional cardiology. Each chapter was designed to focus on the everyday practicability and to provide decision support for cardiologists in the daily clinical routine of a catheter laboratory. Despite the practical advice by many experts, this manual cannot replace the medical evaluation of each individual patient and thus an adaptation of the diagnostics or treatment is necessary.
CRIS-Team WoS Importer:2021-10-08

Multi-Center Comparison of Two Self-Expanding Transcatheter Heart Valves: A Propensity Matched Analysis - Blumenstein, Johannes; Eckel, Clemens; Husser, Oliver; Kim, Won-Keun; Renker, Matthias; Choi, Yeong-Hoon; Hamm, Christian W.; Al-Terki, Hani; Soetemann, Dagmar; Koerbi, Leon; Tiyerili, Vedat; Grothusen, Christina; et al. (Journal of Clinical Medicine, 2022)
Background: During the last years, several transcatheter aortic heart valves entered the clinical market and are commercially available. The prostheses differ regarding several technical and functional aspects. However, little is known regarding head-to-head comparative data of the ACURATE neo and the PORTICO valve prostheses. Objectives: The aim of this study was to compare two self-expanding transcatheter aortic heart valves (THV), the ACURATE neo and the PORTICO, with regard to in-hospital and 30-day outcomes, as well as early device failures. Methods: A total of 1591 consecutive patients with severe native aortic valve stenosis from two centers were included in the analyses and matched by 1:1 nearest neighbor matching to identify one patient treated with PORTICO (n = 344) for each patient treated with ACURATE neo (n = 344). Results: In-hospital complications were comparable between both valves, including any kind of stroke (ACURATE neo = 3.5% vs. PORTICO = 3.8%; p = 1.0), major vascular complications (ACURATE neo = 4.5% vs. PORTICO = 5.4%; p = 0.99) or life-threatening bleeding (ACURATE neo = 1% vs. PORTICO = 2%; p = 0.68). The rate of device failure defined by the VARC-2 criteria were comparable, including elevated gradients and moderate-to-severe paravalvular leakage (ACURATE neo = 7.3% vs. PORTICO = 7.6%; p = 1.0). However, the need for permanent pacemaker implantation (PPI) was significantly more frequent after the use of PORTICO THV (9.5% vs. 18.7%; p = 0.002). Conclusions: In this two-center case-matched comparison, short-term clinical and hemodynamic outcomes showed comparable results between PORTICO and ACURATE neo prostheses. However, PORTICO was associated with a significant higher incidence of PPI.
CRIS-Team WoS Importer:2022-08-12

Myocardial revascularization Controversy over noninvasive and invasive detection of ischemia - Gaede, Luise; Blumenstein, Johannes; Moellmann, Helge (Herz, 2022)
With some exceptions, myocardial revascularization in patients with chronic coronary syndrome (CCS) is generally decided on the basis of the extent of myocardial ischemia. Current data indicate that a patient will benefit from revascularization if ischemia is present in more than 10% of the myocardium. Accordingly, all patients presenting with CCS should undergo a noninvasive ischemia test that can answer this question before diagnostic coronary angiography. In order to be able to make a recommendation for revascularization based on scientific data even in those patients who previously had no clear evidence of ischemia, e.g., because of discrepant findings, measurement of the hemodynamic significance of coronary stenoses with a lumen diameter reduction >= 50% should be performed during coronary angiography. A decision to revascularize based on hemodynamic significance was shown to be beneficial to patients in several studies.
CRIS-Team WoS Importer:2022-05-13

Procedural Outcomes of a Self-Expanding Transcatheter Heart Valve in Patients with Porcelain Aorta - Eckel, Clemens; Blumenstein, Johannes; Grothusen, Christina; Tiyerili, Vedat; Elsaesser, Albrecht; Dohmen, Guido; Zeckzer, Anna; Gaede, Luise; Choi, Yeong-Hoon; Charitos, Efstratios I.; Hamm, Christian W.; Kim, Won-Keun; et al. (Journal of Clinical Medicine, 2023)
Background: Severe calcification of the ascending aorta increases the peri-operative risk for neurological complications in patients with severe aortic stenosis. Transcatheter aortic valve implantation (TAVI) seems to be an optimal treatment option in these patients. However, the impact of the extent of aortic calcification on procedural and neurological outcomes during TAVI is unclear. Methods: Data from 3010 patients with severe native aortic valve stenosis treated with ACURATE neo/neo2 from May 2012 to July 2022 were evaluated and matched by 2-to-1 nearest-neighbor matching to identify one patient with porcelain aorta (PA) (n = 492) compared with two patients without PA (n = 984). PA was additionally subdivided into circumferential (classic PA) (n = 89; 3.0%) and non-circumferential (partial PA) (n = 403; 13.4%) calcification. We compared outcomes according to VARC-3 criteria among patients with and without PA and identified predictors for occurrence of stroke in the overall population. Results: Technical success (88.5% vs. 87.4%, p = 0.589) and device success at 30 days (82.3% vs. 81.5%, p = 0.755) after transcatheter ACURATE neo/neo2 implantation according to VARC-3 definition was high and did not differ between non-calcified aortas or PA. The rate of in-hospital complications according to VARC-3-definitions was low in both groups. Rates of all stroke (3.2% (n = 31) vs. 2.6% (n = 13), p = 0.705) or transitory ischemic attacks (1.1% vs. 1.2%, p =1.000) did not differ significantly. Thirty-day all-cause mortality did not differ (3.0% vs. 3.2%, RR 1.1; p = 0.775). Overall device migration/embolization (OR 5.0 [2.10; 11.87]), severe bleeding (OR 1.79 [1.11; 2.89]), and major structural cardiac complications (OR 3.37 [1.32; 8.57]) were identified as independent predictors for in-hospital stroke in a multivariate analysis after implantation of ACURATE neo/neo2. Conclusion: A porcelain aorta does not increase the risk of neurological complications after transfemoral ACURATE neo/neo2 implantation. Based on these findings, transfemoral ACURATE neo/neo2 implantation is safe in these particularly vulnerable patients.
CRIS-Team WoS Importer:2023-03-10

Radial versus femoral approach for rotational atherectomy - technical aspects and procedural outcomes - Bargon, Sophie; Achenbach, Stephan; Gaede, Luise; Tröbs, Monique; Marwan, Mohamed; Ammon, Fabian; Ferstl, Paul; Schacher, Nora (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Randomized Comparison of Intracoronary Lithotripsy and Rotational Atherectomy for the Treatment of Severely Calcified Vessels-ROTA.shock Trial - Nef, Holger; Schlattner, Sophia; Weissner, Melissa; Gori, Tommaso; Ullrich, Helen; Gaede, Luise; Achenbach, Stephan; Moellmann, Helge; Blumenstein, Johannes; Aksoy, Adem; Nickenig, Georg; Weferling, Maren; et al. (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Rotational atherectomy via the transradial access: success rates, procedural parameters and complications - Ferstl, Paul; Drentwett, Anne-Sophie; Bargon, Sophie; Schacher, Nora; Tröbs, Monique; Marwan, Mohamed; Achenbach, Stephan; Gaede, Luise (Heart and Vessels, 2022)
Radial access is recommended for percutaneous coronary intervention (PCI), but rotational atherectomy remains frequently performed via femoral access. Analyzing the procedural parameters, success rate and complications of rotational atherectomy, performed via radial in comparison to femoral access. We retrospectively analyzed 427 consecutive patients undergoing rotational atherectomy. Procedural parameters and outcome were determined in 171 patients, scheduled for radial and compared to 256 patients with femoral access use. In the radial access group (74 ± 9 years, 84% male), the LAD was most frequently treated (49%). Sheath size was 7F in 59% and 6F in 41%, burr size was 1.5 mm in 46% and 1.25 mm in 14% of patients. A temporary pacemaker was inserted in 14%. Procedural success rate stood at 97%. Access site complications occurred in 4% of patients, which was significantly less frequent than in in 256 patients treated via femoral access (13% p = 0.003). Compared to radial access, femoral access was associated with the use of larger sheaths (p < 0.001), more frequent treatment of non-LAD vessels (58.2% vs. 44.4%, p = 0.013) and a higher rate of temporary pacemaker use (27%; p = 0.001). No differences could be seen in procedural success (p = 0.83) and burr size (p = 0.51). Femoral access (OR 3.33; 95% CI 1.40–7.93), and female sex (OR3.40 95% CI 1.69–6.63) were independent predictors for access site complications. For coronary rotational atherectomy, radial access has a high success rate with overall use of smaller sheaths, but of equally sized burrs as well as a significant lower rate of access site-related complications than femoral access.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Percutaneous coronary intervention; Radial access; Rotational atherectomy; Transradial

Schwangerschaft und Mutterschutz in der Kardiologie und in der Kinder- und Jugendkardiologie - Güder, Gülmisal; Boer, Jana; Busch, Sonia; Gaede, Luise; Graf, Tobias; Herberg, Ulrike; Kretschmer, Angela; Krüger, Martina; Lerchenmüller, Carolin; Merbecks, Moritz; Nebe, Katja; Neizel-Wittke, Mirja; et al. (Die Kardiologie, 2024)
Women in cardiology and pediatric cardiology are exposed to special health risks that may call into question their continued employment during the protected time and may result in company employment bans. Pregnant, breastfeeding and recently postpartum women are subject to special legal protection to protect themselves and their children from irresponsible endangerment and occupational discrimination. The aim of this consensus paper of the German Cardiac Society, the German Society of Pediatric Cardiology and Congenital Heart Defects and the German Society for Occupational Medicine and Environmental Medicine is to present the legal framework of the Maternity Protection Act and to discuss adaptation and redesign options of the working conditions during pregnancy and breastfeeding to enable unrestricted occupational participation and avoid blanket employment bans and the resulting career losses and delays in further training.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Company employment ban; Maternity Protection Act; Radiation protection; Specialist training regulations; Working time regulations

Side effects and major adverse cardiac events caused by fractional flow reserve measurement: a systematic review and meta-analysis of 12,215 patients - Altstidl, Johannes Michael; Gaede, Luise; Tröbs, Monique; Marwan, Mohamed; Achenbach, Susanne (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Timing of Complete Revascularization with Multivessel PCI for Myocardial Infarction. - Stähli, Barbara E.; Varbella, Ferdinando; Linke, Axel; Schwarz, Bettina; Felix, Stephan B.; Seiffert, Moritz; Kesterke, Rahel; Nordbeck, Peter; Witzenbichler, Bernhard; Lang, Irene M.; Kessler, Mirjam; Valina, Christian; et al. (New England Journal of Medicine, 2023)
Background In patients with ST-segment elevation myocardial infarction (STEMI) with multivessel coronary artery disease, the time at which complete revascularization of nonculprit lesions should be performed remains unknown. Methods We performed an international, open-label, randomized, noninferiority trial at 37 sites in Europe. Patients in a hemodynamically stable condition who had STEMI and multivessel coronary artery disease were randomly assigned to undergo immediate multivessel percutaneous coronary intervention (PCI; immediate group) or PCI of the culprit lesion followed by staged multivessel PCI of nonculprit lesions within 19 to 45 days after the index procedure (staged group). The primary end point was a composite of death from any cause, nonfatal myocardial infarction, stroke, unplanned ischemia-driven revascularization, or hospitalization for heart failure at 1 year after randomization. The percentages of patients with a primary or secondary end-point event are provided as Kaplan-Meier estimates at 6 months and at 1 year. Results We assigned 418 patients to undergo immediate multivessel PCI and 422 to undergo staged multivessel PCI. A primary end-point event occurred in 35 patients (8.5%) in the immediate group as compared with 68 patients (16.3%) in the staged group (risk ratio, 0.52; 95% confidence interval, 0.38 to 0.72; P<0.001 for noninferiority and P<0.001 for superiority). Nonfatal myocardial infarction and unplanned ischemia-driven revascularization occurred in 8 patients (2.0%) and 17 patients (4.1%), respectively, in the immediate group and in 22 patients (5.3%) and 39 patients (9.3%), respectively, in the staged group. The risk of death from any cause, the risk of stroke, and the risk of hospitalization for heart failure appeared to be similar in the two groups. A total of 104 patients in the immediate group and 145 patients in the staged group had a serious adverse event. Conclusions Among patients in hemodynamically stable condition with STEMI and multivessel coronary artery disease, immediate multivessel PCI was noninferior to staged multivessel PCI with respect to the risk of death from any cause, nonfatal myocardial infarction, stroke, unplanned ischemia-driven revascularization, or hospitalization for heart failure at 1 year. (Supported by Boston Scientific; MULTISTARS AMI ClinicalTrials.gov number, NCT03135275.)
CRIS-Team Scopus Importer:2023-12-08
Keywords: Cardiology; Cardiology General; Coronary Disease/Myocardial Infarction

Towards a FHIR-Based Data Model for Coronary Angiography Observations - Holweg, Florian; Achenbach, Stephan; Deppenwiese, Noemi; Gaede, Luise; Prokosch, Hans-Ulrich (Healthcare of the Future 2022, 2022)
Coronary heart disease is among the most frequent causes of death globally. Thus, our research project aims to develop prognostic models, to predict the risk of spontaneous myocardial infarctions based on a combination of clinical parameters and image data sets (invasive coronary angiograms). To train such models we use data from more than 30,000 coronary angiograms acquired at the cardiology department of Erlangen University Hospital. To linking such proprietary data with additional clinical parameters and to harmonize it for future cross-hospital federated machine learning approaches we defined a mapping for coronary angiography based on the symptom/ clinical phenotype HL7® FHIR® module of the German medical informatics initiative. In this paper we describe the final design of the coronary angiography information model and our mapping approach to ICD-10 and SNOMED CT. From the database we use a subset of 15 required values patient characteristics to create the HL7® FHIR® resource.
CRIS-Team Scopus Importer:2022-05-27
Keywords: coronary angiography; data model; HL7 FHIR; SNOMED CT

Transcatheter-based aortic valve replacement vs. isolated surgical aortic valve replacement in 2020 - Gaede, Luise; Blumenstein, Johannes; Eckel, Clemens; Grothusen, Christina; Tiyerili, Vedat; Soetemann, Dagmar; Nef, Holger; Elsaesser, Albrecht; Achenbach, Stephan; Moellmann, Helge (Clinical Research in Cardiology, 2022)
Background: Based on the results of several recent randomized trials, European and American guidelines on valvular heart disease management have substantially expanded the indications for transcatheter aortic valve implantation (TAVI). We present an all-comer data on peri-operative risk profile and in-hospital outcomes from Germany for patients treated by TAVI or isolated surgical aortic valve replacement (iSAVR) in 2020, providing an opportunity to compare study data with data from daily clinical practice. Methods: Data concerning all isolated aortic valve procedures performed in Germany in 2020 were retrieved from the mandatory nationwide quality control program. Expected mortality was calculated with the annually revised German Aortic valve score (AKL-score) based on the data of either catheter-based (AKL-CATH) or isolated surgical (AKL-CHIR) aortic valve replacement in Germany from the previous year (2019). Results: In 2020 21,903 TAVI procedures (20,810 transvascular (TV; vs. 2019: 22.973; − 9.4%), 1093 transapical (TA; vs. 2019: 1413; − 22.6%)) and 6144 (vs. 2019 7905; − 22.5%) iSAVR were performed in Germany. Patients who received TAVI showed a significantly higher perioperative risk profile than patients undergoing iSAVR based on older age and more severe co-morbidities. While in-hospital mortality after TAVI (2.3%) was numerically lower than in 2019 (2.5%), this difference was not significant (p = 0.11). In-hospital mortality after iSAVR was identical in 2020 and 2019 (2.8%) and thus higher than after TAVI (p = 0.003), resulting in an observed expected mortality ratio of 1.02 after TAVI and 1.05 after iSAVR. After exclusion of the emergency procedures, in-hospital mortality did not differ significantly between the groups (TAVI 2.2% vs. iSAVR 1.9%, p = 0.26). Conclusion: Total numbers of both iSAVR and TAVI in Germany were lower in 2020 than in 2019, most likely due to the COVID-19 pandemic. However, the relative number of patients treated by TAVI as compared to iSAVR continues to increase. Despite older age and more severe comorbidities compared to patients undergoing iSAVR the in-hospital mortality after TAVI continued to decrease in 2020 and remains significantly lower than after iSAVR. Graphical Abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-04-15
Keywords: Aortic valve replacement; Real world; Registry; TAVI; TAVR

Use of coronary physiology to guide revascularization in clinical practice: results of the F(FR)2 registry - Altstidl, Johannes Michael; Achenbach, Stephan; Feyrer, Johannes; Nazli, J. Benedikt; Marwan, Mohamed; Gaede, Luise; Möllmann, Helge; Giesler, Tom; Rittger, Harald; Pauschinger, Matthias; Rudolph, Tanja K.; Moshage, Werner; et al. (Clinical Research in Cardiology, 2024)
Background: Despite the recommendation of coronary physiology to guide revascularization in angiographically intermediate stenoses without established correlation to ischemia, its uptake in clinical practice is slow. Aims: This study aimed to analyze the use of coronary physiology in clinical practice. Methods: Based on a multicenter registry (Fractional Flow Reserve Fax Registry, F(FR)2, ClinicalTrials.gov identifier NCT03055910), clinical use, consequences, and complications of coronary physiology were systematically analyzed. Results: F(FR)2 enrolled 2,000 patients with 3,378 intracoronary pressure measurements. Most measurements (96.8%) were performed in angiographically intermediate stenoses. Out of 3,238 lesions in which coronary physiology was used to guide revascularization, revascularization was deferred in 2,643 (78.2%) cases. Fractional flow reserve (FFR) was the most common pressure index used (87.6%), with hyperemia induced by an intracoronary bolus of adenosine in 2,556 lesions (86.4%) and intravenous adenosine used for 384 measurements (13.0%). The route of adenosine administration did not influence FFR results (change-in-estimate -3.1% for regression model predicting FFR from diameter stenosis). Agreement with the subsequent revascularization decision was 93.4% for intravenous and 95.0% for intracoronary adenosine (p = 0.261). Coronary artery occlusion caused by the pressure wire was reported in two cases (0.1%) and dissection in three cases (0.2%), which was fatal once (0.1%). Conclusions: In clinical practice, intracoronary pressure measurements are mostly used to guide revascularization decisions in angiographically intermediate stenoses. Intracoronary and intravenous administration of adenosine seem equally suited. While the rate of serious complications of wire-based intracoronary pressure measurements in clinical practice seems to be low, it is not negligible. Graphical abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-06-14
Keywords: Complications; Coronary artery disease; Coronary physiology; Fractional flow reserve (FFR); Registry